2016
DOI: 10.7314/apjcp.2016.17.4.1829
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Screening of BRCA1 Mutations (185delAG, 1294del40) in Nepalese Breast Cancer Patients

Abstract: Background: Breast cancer is the second most common malignancy among Nepalese women, accounting for 60% of the total cancer cases in females. Women diagnosed with germline mutations in BRCA1 like 185delAG, 1294del40 develop breast and/or ovarian cancer with a lifelong likelihood of up to 85% whereas presence of a mutation increases the risk for mutations to occur in other genes. The major objective of this study was to find the prevalence of these mutations in Nepalese cancer patients. Materials and Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The mean age at diagnosis of our patients is close to the mean age at testing of women of African descent (45.2 years) but lower than that of the Asian descent (47.1 years) and European women (50 years) (Hall et al, 2009). Bhatta (2016) reported the mean age of onset of breast cancer was 42.59 years and found 8% of BRCA1 mutation in his study population in Nepal. Another study in Nepal reported older age (mean age 46.50 years) of onset (Singh and Sayami, 2009) than that of Bhatta (2016).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The mean age at diagnosis of our patients is close to the mean age at testing of women of African descent (45.2 years) but lower than that of the Asian descent (47.1 years) and European women (50 years) (Hall et al, 2009). Bhatta (2016) reported the mean age of onset of breast cancer was 42.59 years and found 8% of BRCA1 mutation in his study population in Nepal. Another study in Nepal reported older age (mean age 46.50 years) of onset (Singh and Sayami, 2009) than that of Bhatta (2016).…”
Section: Discussionsupporting
confidence: 65%
“…Bhatta (2016) reported the mean age of onset of breast cancer was 42.59 years and found 8% of BRCA1 mutation in his study population in Nepal. Another study in Nepal reported older age (mean age 46.50 years) of onset (Singh and Sayami, 2009) than that of Bhatta (2016). The mean age of onset was 47.50 years in the North Indian women (Singh et al, 2015) is higher than the age at diagnosis of our population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…21 Similarly, a pilot study Screening of BRCA1 Mutations (185delAG, 1294del40) in Nepalese breast cancer patients showed that BRCA1 Mutations (185delAG) was 8 %. 22…”
Section: Family Historymentioning
confidence: 99%
“…The hereditary cancer burden in Nepal is unknown, however a recent study of 50 women with breast cancer diagnosed in Kathmandu found the prevalence of a single mutation ( BRCA1 185delAG) to be 8%, which is considerably higher than in unselected breast cancer cases in a western population [14], suggesting that hereditary cancer may be just as common, if not more so, than in other populations. Compared with the western developed countries, genetic testing and risk assessment for familial cancer in Asia has been shown to be less available, thus prohibiting the appropriate surveillance, clinical strategies and cancer management of patients and their relatives [15].…”
Section: Introductionmentioning
confidence: 99%